2003
DOI: 10.1097/01.sla.0000055269.77838.8e
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of a Randomized Prospective Study Comparing Medical and Surgical Treatment of Barrett’s Esophagus

Abstract: These results show that there are no differences between the two types of treatment with respect to preventing BE from progressing to dysplasia and adenocarcinoma. However, successful antireflux surgery proved to be more efficient than medical treatment in this sense, perhaps because it completely controls acid and biliopancreatic reflux to the esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
129
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 26 publications
(36 reference statements)
5
129
1
8
Order By: Relevance
“…One relatively small randomized trial showed no diff erence in progression outcomes between medical and surgical groups ( 169 ), but this result is susceptible to type II error. Meta-analyses on the subject reveal confl icting results, in that some authors have found no diff erence in cancer risk between medically and surgically managed patients, whereas others show some suggestion of improved outcomes in surgically treated patients (170)(171)(172).…”
Section: Surgical Therapymentioning
confidence: 94%
“…One relatively small randomized trial showed no diff erence in progression outcomes between medical and surgical groups ( 169 ), but this result is susceptible to type II error. Meta-analyses on the subject reveal confl icting results, in that some authors have found no diff erence in cancer risk between medically and surgically managed patients, whereas others show some suggestion of improved outcomes in surgically treated patients (170)(171)(172).…”
Section: Surgical Therapymentioning
confidence: 94%
“…There were not enough patients in the surgical arm to determine if this was a significant difference. Parrilla et al have published the only randomized study comparing 43 patient treated with medical treatment and 58 with antireflux surgery (Parrilla et al 2003). In that study, 101 patients with BE were treated between 1982 and 2000.…”
Section: Barrett's Esophagusmentioning
confidence: 99%
“…This is partly due to the fact that medical therapy with proton pump inhibitors (PPIs) seem to provide a 93% symptom remission (Lundell et al, 2008), and studies that show both medical and surgical treatments are highly effective, safe and well tolerated (Mahon et al, 2005;Ortiz et al, 1996;Parrilla et al, 2003;Spechler, 1992;Spechler et al, 2001) and improve QoL of GERD patients. Gillies and colleagues (Gillies et al, 2008) showed that laparoscopic anti-reflux surgery also improved the QoL of patients whose symptoms were well controlled on medical therapy.…”
Section: Symptomsmentioning
confidence: 99%